Organ-specific transcriptional regulation by HFR1 and HY5 in response to shade in Arabidopsis - Choi, Ian Kin Yuen; Chaturvedi, Amit Kumar; Sng, Benny Jian Rong; Vu, Kien Van; Jang, In-Cheol (Frontiers in Plant Science, 2024)
Light is crucial for plants and serves as a signal for modulating their growth. Under shade, where red to far-red light ratio is low, plants exhibit shade avoidance responses (SAR). LONG HYPOCOTYL IN FAR-RED 1 (HFR1) and ELONGATED HYPOCOTYL 5 (HY5) are known to be negative regulators of SAR and physically interact with one another. However, transcriptional regulatory network underlying SAR by these two transcription factors has not been explored. Here, we performed organ-specific transcriptome analyses of Arabidopsis thaliana hfr1-5, hy5-215 and hfr1hy5 to identify genes that are co-regulated by HFR1 and HY5 in hypocotyls and cotyledons. Genes co-regulated by HFR1 and HY5 were enriched in various processes related to cell wall modification and chlorophyll biosynthesis in hypocotyls. Phytohormone (abscisic acid and jasmonic acid) and light responses were significantly regulated by HFR1 and HY5 in both organs, though it is more prominent under shade in cotyledons. HFR1 and HY5 also differentially regulate the expression of the cell wall-related genes for xyloglucan endotransglucosylase/hydrolase, expansin, arabinogalactan protein and class III peroxidase depending on the organs. Furthermore, HFR1 and HY5 cooperatively regulate hypocotyl responsiveness to shade through auxin metabolism. Together, our study illustrates the importance of the HFR1-HY5 module in regulating organ-specific shade responses in Arabidopsis.